Mechanism Of Determining And Collection Motor Vehicle Tax - Andi Rustam; M. Hidayat; Rezky Firmansyah Hr (Universitas Muhammadiyah Makassar, 2023)
This study aims to find out the procedures for determining motor vehicle tax and to find out the mechanism for implementing and collecting motor vehicle tax at the Regional Revenue Agency Office of South Sulawesi Province This research data collection technique is to conduct library studies and interviews directly to the parties used as informants. The results of this study revealed that at the time before the taxation of motor vehicles, it is necessary to check the identity of the vehicle starting from the inspection of the vehicle's brand, vehicle type and vehicle manufacturing year. Tax will be collected at the Samsat Office